Phyotherapeutic Properties of Urfa Pistachio Nuts (Pistacia vera L.) - İsmail KOYUNCU; Abdurrahim KOÇYİĞİT; Reşat DİKME; Şahbettin SELEK (Bezmiâlem Science, 2018)

(untitled)
According to recent studies, the Urfa pistachio nut (Pistacia vera L.) is a rich source of phenolic components, with a high level of the three antioxidant substances of gallic acid, catechin, and epicatechin present together. The pistachio nut, which is in the top 50 foodstuffs with the highest antioxidant potential, is the only edible nut containing anthocyanin, which is the richest and has most variations of water and fat-soluble antioxidants. The pistachio nut also contains important bioactive polyphenol components, such as transreservatrol and isoflavones, which have anti-cancer potential. Some forms of the Pistachio species, including the Urfa pistachio nut, are used by the general population to improve the gastrointestinal, liver, urinary tract, and respiratory tract disorders and for various other purposes such as aphrodisiac, antiseptic, and antihypertensive effects. In some studies, it has been determined that the pistachio nut is beneficial in the continuation of mechanisms that provide maintenance of body health, such as anti-inflammatory activity, glycemic control, and endothelial functions, and it has also been shown to prevent the oxidation of low-density lipoprotein cholesterol and to have a protective role against chronic diseases such as cancer and cardiovascular disease. With a potassium content of 10.05 mg/gram, which is higher than other types of peanut, the sodium content of the pistachio nut may play a role in balancing the blood pressure by reducing the need for salt. This review is of importance in respect of the evaluation of the positive effect on several diseases of the kernel and particularly the shell extract of the pistachio nut.